2021
DOI: 10.1186/s12873-021-00531-2
|View full text |Cite
|
Sign up to set email alerts
|

A dangerously underrated entity? Non-specific complaints at emergency department presentation are associated with utilisation of less diagnostic resources

Abstract: Background Patients presenting with non-specific complaints (NSC), such as generalised weakness, or feeling unwell, constitute about 20% of emergency care consultations. In contrast to patients presenting with specific symptoms, these patients experience more hospitalisations, longer stays in hospital and even higher mortality. However, little is known about the actual resources spent on patients with NSC in the emergency department (ED). Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The present study showed that a variety of diseases can cause difficulties in movement. As no clear diagnostic algorithm has yet been established for emergency patients transported for a chief complaint of difficulty moving 32) , the present findings suggest the importance of obtaining the patient's history, evaluating vital signs, conducting a physical examination, laboratory examinations including blood culture, and physiological and radiological studies, including computed tomography.…”
Section: Discussionmentioning
confidence: 86%
“…The present study showed that a variety of diseases can cause difficulties in movement. As no clear diagnostic algorithm has yet been established for emergency patients transported for a chief complaint of difficulty moving 32) , the present findings suggest the importance of obtaining the patient's history, evaluating vital signs, conducting a physical examination, laboratory examinations including blood culture, and physiological and radiological studies, including computed tomography.…”
Section: Discussionmentioning
confidence: 86%
“…However, in the case of nonspecific complaints, since not all of them appear to be more frequent among those with dementia, this will likely require interim work on better definition and identification for chief complaint standardization. Current standards (including this study as exploratory work with a novel data set) largely use physician review to distinguish nonspecific from specific complaints 46,47 …”
Section: Discussionmentioning
confidence: 99%
“…Diverse presentations: Patients in the emergency department present with a diverse array of medical conditions, from minor or nonspecific complaints to life-threatening emergencies. This diversity demands a wide range of diagnostic and treatment decisions [ 13 , 14 ].…”
Section: Reviewmentioning
confidence: 99%